Is panoramic radiography reliable to evaluate the relationship between maxillary molar and premolar roots and the maxillary sinus? (Research, Society and Development, 2023)
Aim: To evaluate the radiographic signs of proximity relationship between maxillary molar roots and maxillary sinus in panoramic radiographs, using CBCT as control. Methods: 81 examinations of patients who had panoramic radiographs and CBCT of the maxillary molars and pre molars region were used. Pathological situations were excluded from this study. Panoramic radiographs and CBCT were evaluated randomly and separately by an experienced dental radiology examiner. 1,055 root apices were evaluated individually. When assessing the relationship between maxillary molar and pre molar apices, and maxillary sinus, the examiner rated the images, both in panoramic radiography and CBCT, according to a scale of 0 to 3, where 0–Without relationship or distant; 1-Root apex projection or overlapping; 2-Maxillary sinus circumventing the tooth root; 3-Interruption of the continuity of maxillary sinus floor. Tabulated data were statistically analyzed using Kappa test and interclass correlation coefficient (ICC) respectively, with a significance level of 5%. A second analysis of the sample was performed after 15 days to analyze reproducibility. Results: Kappa test indicated near perfect reproducibility (Kw=0.973). The highest prevalence ratio, when comparing the classification in panoramic radiographs and CBCT, was for type 1 (52,7%). There was no difference between the type 1 signal and the gold standard observed on CBCT (ρ=0.2152). Conclusion: Panoramic radiography can be used to evaluate the relationship between roots of maxillary molars and premolars with the maxillary sinus. For cases where there is overlapping between apices and maxillary sinus, CBCT remains the indicated exam for better evaluation.